Distinct roles of α- and βCaMKII in controlling long-term potentiation of GABAA-receptor mediated transmission in murine Purkinje cells - Gao, Zhenyu; van Woerden, Geeske M.; Elgersma, Ype; De Zeeuw, Chris I.; Hoebeek, Freek (Frontiers in Cellular Neuroscience, 2014)
Calcium/Calmodulin-dependent kinase type II (CaMKII) is essential for various forms of synaptic plasticity. The predominant α- and βCaMKII isoforms have both been shown to contribute to specific forms of plasticity at excitatory synapses, but little is known about their functions at inhibitory synapses. Here we investigated the role of both isoforms in long-term potentiation of the inhibitory molecular layer interneuron to Purkinje cell synapse (MLI-PC iLTP) upon climbing fiber (CF) stimulation. We demonstrate that deleting either the α- or βCaMKII isoform affected MLI-PC iLTP. In the presence of the PP2B blocker cyclosporin A, CF stimulation elicited iLTP in Camk2b-/- mice, but not in Camk2a-/- mice. Moreover, co-activation of the MLIs and CF suppressed iLTP in wild-type mice through activation of GABAB-receptors, whereas it evoked iLTP in Camk2b-/-. This reversal of the effect of αCaMKII activity in Camk2b-/- mutants upon co-activation did not critically involve protein kinase A, but depended on calcium release from internal stores. Our results indicate that α- and βCaMKII isoforms in Purkinje cells can be differentially activated and serve distinct roles in controlling iLTP. We propose that the CaMKII holo-enzyme may be selectively activated by various GABAB-mediated pathways and that the presence of the βCaMKII isoform determines their impact on inhibitory plasticity.